A visual art intervention program for older people with stroke in residential care settings: A feasibility study. - Pang, Chui Ping Phyllis; Cheung, Daphne Sze Ki; Chiang, Vico Chung Lim (Scandinavian Journal of Caring Sciences, 2024)
Introduction: Stroke poses challenges to the physiological, psychosocial and spiritual well‐being of affected individuals. As the impacts of stroke might not be reversible, a shift in focus to providing care is desirable. Visual art interventions using visual and symbolic art can help participants to express their feelings, give them a sense of choice and the feeling that they are retaining a sense of control, promote insights, restructure their sense of cognition and instil hope. There have been few studies on visual art interventions involving older people with stroke and none in residential care homes (RCHs). Theoretical support and rigorous research designs on the subject are lacking. Thus, this study seeks to address this research gap by examining the feasibility of a visual art intervention for older people in RCHs and exploring the impacts on their holistic well‐being. Methods: This was a single‐blinded, two‐arm, randomised controlled feasibility study grounded on Watson's Caring Theory. The Holistic Well‐Being Scale and Caring Factor Survey were used in the study, with three assessment time‐points: before the intervention (T1), at the mid‐point of the intervention (T2) and immediately after the intervention (T3). Results: Sixty‐one older people with stroke were recruited from 14 RCHs and randomised into the intervention and control groups. The recruitment rate was 44.53%, and the retention rate for the intervention group was 93.55%. Implementing the programme was affordable (at approximately US$126/head), the duration was acceptable (721 min) and the feedback from participants and staff of the RCHs was positive. Conclusions: The visual art intervention programme proved to be clinically feasible. This study adds new insights to the development of visual art interventions and to the caring sciences. The efficacy of the programme on holistic well‐being has yet to be confirmed.